SUMO modification of Rad22, the Schizosaccharomyces pombe homologue of the recombination protein Rad52 - Ho, Jenny C. Y. (Oxford University Press, 2001)
The Schizosaccharomyces pombe rad31 and hus5 genes are required for the DNA damage response, as mutants defective in these genes are sensitive to DNA damaging agents, such as UV and ionising radiation and to the DNA synthesis inhibitor hydroxyurea (HU). Sequence analysis has suggested that rad31 and hus5 encode components of the Pmt3 (SUMO) modification process in S.pombe. We show here that the rad31 null and hus5.62 mutants display reduced levels of Pmt3 modification. We have initiated a search for proteins required for the DNA damage response, which may be modified by Pmt3 and have identified Rad22, the fission yeast homologue of the recombination protein Rad52. Purification of myc + His-tagged Rad22 protein from cells expressing HA-tagged Pmt3 identifies an 83 kDa species which cross-reacts with anti-HA antisera. We show here that Rad22 interacts with Rhp51 and Rpa70 (the fission yeast homologues of Rad51 and the large subunit of RPA, respectively), but that neither of these proteins appears to be responsible for the 83 kDa species. The 83 kDa species is observed when extracts are prepared under both native and denaturing conditions, and is also observed when myc + His-tagged Rad22 and Pmt3 are expressed at wild type levels, suggesting that Rad22 is modified by Pmt3 in vivo. We have established an S.pombe in vitro Pmt3 modification system and have shown that Rad22 and Rhp51 are modified in vitro, but that Rpa70 is not.